In Silico Study of Secondary Metabolite Compound from Noni fruit (Morinda citrifolia) as Potential Drug Candidates for Type 2 Diabetes Mellitus Targeting PPAR-γ - Rasya Salma Fauziyyah; Stella Aurelia Huang; Apsari Maratus Sholehah; Tribuana Tungga Dewi; Rina Fajri Nuwarda (Indonesian Journal of Chemical Science, 2025)
Diabetes type 2 is a chronic metabolic disorder characterized by an increase of blood sugar levels in the body due to insufficient insulin resistance. Noni (Morinda citrifolia L) is a medicinal plant that can be used as an alternative treatment for diabetes. One receptor involved in diabetes treatment is Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ), which plays a role in insulin sensitization in adipose tissue. This in silico study investigates the potential of noni fruit using Lipinski's Rule of Five (RO5) prediction, ADME-Tox prediction, and molecular docking to identify several metabolites with strong binding affinity to PPAR-γ. The results indicate that rutin violates Lipinski's Rule of Five and has an HIA value of 2.861176%, making it poorly absorbed orally and more suitable for non-oral formulations. The KI value of 4.19 µM and the amino acid interactions most similar to the natural ligand indicate that rutin shows a strong binding affinity to PPAR-γ, demonstrating its potential efficacy as an antidiabetic agent.